Influence of Zr and Be on microstructure and electrochemical behavior of AZ63 anode. Issue 4 (25th October 2018) - Jafari, Hassan; Mohammad Hassanizadeh, Behrouz
Abstract : In this study, the effect of Zr and Be on the microstructure and electrochemical properties of a common magnesium alloy anode, AZ63, used in cathodic protection, was investigated. The AZ63, as well as Zr (0.25, 0.50, 0.70, and 0.90 wt%) and Be (0.0001, 0.001, 0.01, and 0.1 wt%) bearing AZ63 anodes, were prepared. The microstructure and electrochemical characteristics of the cast anodes were characterized. The results showed that the addition of Zr refines the grain size of the AZ63 anode; and above 0.5 wt% Zr, forms Al2 Zr and β‐Mg17 Al12 . In contrast, grain coarsening was observed with increasing Be content. Moreover, the addition of 0.1 wt% Be to the anode resulted in the spheroidization of the β‐phase. Also, it was shown that AZ63‐0.5 wt% Zr provides the lowest corrosion rate among the experimented anodes, and the higher the Be content, the lower the corrosion rate of the anode. Higher content of both Be and Zr alloying elements resulted in improved efficiency of the anode for 20% and 13%, respectively. The results of this study indicate higher impact of Be on the efficiency increment of the AZ63 anode. Abstract : In this study, the effect of Zr and Be on the microstructure and electrochemical properties of a common magnesium alloy anode, AZ63, used in cathodic protection, was investigated. It was shown that AZ63‐0.5 wt% Zr provides the lowest corrosion rate, and the higher the Be content, the lower the corrosion rate of the anode. Higher content of both Be and Zr alloying elements resulted in improved efficiency of the anode for 20% and 13%, respectively.